2010
DOI: 10.1111/j.1600-0765.2009.01237.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of MMP-2 at the interface between epithelial cells and fibroblasts from human periodontal ligament

Abstract: These findings indicate that putative epithelial rests of Malassez cells stimulate the production of MMP-2 in human periodontal ligament fibroblasts. Up-regulated proMMP-2 bound by MMP-14 expressed in epithelial rests of Malassez cells can degrade matrix molecules, such as type IV collagen, in the basal membrane between putative epithelial rests of Malassez cells and human periodontal ligament fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…MMPs are a class of proteolytic enzymes that function to cleave and degrade collagens and other ECM proteins. PDL fibroblasts express several members of this protease family, including MMP1, MMP2, MMP3, MMP8, and MMP9 40‐43 . Several MMPs are upregulated during the inflammation‐driven tissue destruction of periodontal disease, including MMP1, MMP2, MMP8, and MMP9 44,45 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMPs are a class of proteolytic enzymes that function to cleave and degrade collagens and other ECM proteins. PDL fibroblasts express several members of this protease family, including MMP1, MMP2, MMP3, MMP8, and MMP9 40‐43 . Several MMPs are upregulated during the inflammation‐driven tissue destruction of periodontal disease, including MMP1, MMP2, MMP8, and MMP9 44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…PDL fibroblasts express several members of this protease family, including MMP1, MMP2, MMP3, MMP8, and MMP9. [40][41][42][43] Several MMPs are upregulated during the inflammation-driven tissue destruction of periodontal disease, including MMP1, MMP2, MMP8, and MMP9. 44,45 Smoking increases the activity of MMP8 and MMP9 in patients with chronic periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were also incubated overnight at 4°C with primary antibodies to polyclonal rabbit anti‐porcine amelogenin (117‐81‐2b) (0.1 μg ml −1 ), polyclonal rabbit anti‐porcine ameloblastin (214) (0.1 μg ml −1 ) (courtesy of Dr Takashi Uchida, Department of Oral Biology, Division of Molecular Medical Science, Hiroshima University Graduate School of Biomedical Science, Hiroshima, Japan), monoclonal mouse anti‐human MMP‐20 (5 μg ml −1 ) (Daiichi Fine Chemical, Toyama, Japan), and monoclonal mouse anti‐human KLK‐4 (25 μg ml −1 ) (R&D Systems, Minneapolis, MN, USA). The sequence specificity of amelogenin and ameloblastin antibodies used in this study was conserved between mouse and human . The samples were subsequently incubated with secondary antibody to biotinylated immunoglobulin at room temperature for 30 min and visualized by the avidin‐biotinylated peroxidase complex (ABC) procedure using an ExtrAvidin peroxidase staining kit (Sigma‐Aldrich) and an AEC (3‐amino‐9‐ethylcarbazole) chromogen kit (Sigma‐Aldrich), according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…We have reported that epithelial–mesenchymal interactions modulate the expression of alkaline phosphatase, osteocalcin, and bone sialoprotein at the interface between the epithelial cells and fibroblasts from human periodontal ligament . Furthermore, we showed that their interactions modulate the basement membrane for maintaining homeostasis of the periodontium at the interface space . On the other hand, their interactions do not mediate the basement membrane of cementum formation, because the basement membrane of Hertwig's epithelial root sheath is disrupted when cementoblasts start to form acellular cementum.…”
mentioning
confidence: 86%
“…Matrix metalloproteinases 2 and 9 were also shown to be induced during the development of inflammatory periapical lesions (34). Using in situ hybridization analysis it was demonstrated that human periodontal ligament fibroblasts expressed matrix metalloproteinase-2 mRNA, whereas putative epithelial cell rests of Malassez expressed matrix metalloproteinase-14 mRNA at the interface between epithelial cells and fibroblasts (194). In the inflammatory response of oral epithelial cells to F. nucleatum, Mahtout et al (127) detected up-regulated gene expression and protein secretion of interleukin-6, interleukin-8 and matrix metalloproteinase-9.…”
Section: Matrix Metalloproteinases 2 Andmentioning
confidence: 99%